alpha(1)-Adrenoceptors in proximal segments of tail arteries from control and reserpinised rats - Kamikihara, Susana Y. [UNESP]; Mueller, Andre [UNESP]; Lima, Vanessa [UNESP]; Akinaga, Juliana [UNESP]; Nojimoto, Fernanda D. [UNESP]; Castilho, Anthony [UNESP]; Buratini, Jose [UNESP]; Pupo, Andre S. [UNESP] (Springer, 2007)
It has been recently shown that the supersensitivity of distal segments of the rat tail artery to phenylephrine after chemical sympathectomy with reserpine results from the appearance of alpha(1D)-adrenoceptors. It is known that both alpha(1A)- and alpha(1D)-adrenoceptors are involved in the contractions of proximal portions of the rat tail artery. Therefore, this study investigated whether sympathectomy with reserpine would induce supersensitivity in proximal segments of the rat tail artery, a tissue in which alpha(1D)-adrenoceptors are already functional. Proximal segments of tail arteries from reserpinised rats were three- to sixfold more sensitive to phenylephrine and methoxamine than were arteries from control rats (n=6-2; p<0.05). The imidazolines N-[5-(4,5-Dihydro-1H-imidazol-2-yl)-2-hydroxy-5,6,7,8-tetrahydronaphthalen-1-yl]methanesulfonamide hydrobromide (A-61603) and oxymetazoline, which activate selectively alpha(1A)-adrenoceptors, were equipotent in tail arteries from control and reserpinised rats (n=4-2; p<0.05), whereas buspirone, which activates selectively alpha(1D)-adrenoceptor, was approximate to 4-fold more potent in tail arteries from reserpinised rats (n=4-6; p<0.05). Prazosin (nonselective) and 5- methylurapidil (alpha(1A)- selective), were competitive antagonists of contractions induced by phenylephrine and were equipotent in tail arteries from control and reserpinised rats (n=4-6). The selective alpha(1D)-adrenoceptor antagonist 8[ 2-[4-(2-methoxyphenyl)-1-piperazinyl]ethyl]-8-azaspiro[4.5]decane-7,9-dione dihydrochloride (BMY-7378) presented similar complex antagonism in tail arteries from control and reserpinised rats, with Schild slopes much lower than 1.0 (p<0.05, n=4-6). Semiquantitative reverse transcriptase polymerase chain reaction (RT-PCR) revealed that mRNA encoding alpha(1A)- and alpha(1B)-adrenoceptors are similarly distributed in tail arteries from control and reserpinised rats, whereas mRNA for alpha(1D)-adrenoceptors is twice more abundant in the tail artery from reserpinised rats. In conclusion, the supersensitivity induced by reserpine is related only to alpha(1D)-adrenoceptors, even in tissues where this receptor subtype is already present and functional. Only the use of subtype-selective alpha(1)-adrenoceptor agonists detected the increased alpha(1D)-adrenoceptor component after reserpinisation, as the antagonists behaved similarly in tail arteries from control and reserpinised rats.
Keywords: alpha(1)-adrenoceptors; alpha(1D)-adrenoceptors; alpha(1)-adrenoceptor agonists; Rat tail artery; Reserpine; Sympathectomy